ChemInform Abstract: Total Synthesis of Phenanthroindolizidine Alkaloids via Asymmetric Deprotonation of N‐Boc‐pyrrolidine. Issue 49 (9th December 2014) - Deng, Meng; Su, Bo; Zhang, Hui; Liu, Yuxiu; Wang, Qingmin
Abstract A stereoselective synthesis of (+)‐antofine (I) and (+)‐14‐hydroxyantofine (II) is presented.